PERLINDUNGAN HUKUM BAGI PELAKU USAHA DALAM METODE TRANSAKSI COD CEK DULU - Fahrul Arifin; Fahrur Rosi; Sumriyah (JOURNAL SAINS STUDENT RESEARCH, 2023)
Legal protection must be strictly regulated in law to protect the unfulfilled rights of consumers and business actors in online buying and selling transactions. Business actors on the PT platform. Shopee Indonesia experienced non-fulfillment of its rights in the Cash On Delivery (COD) payment method, namely the right to receive payment according to the Cash On Delivery (COD) agreement. So regarding the conditions and exchange value of goods or services being bought and sold, they receive legal protection from consumer actions that do not comply with the agreement in Cash On Delivery (COD), which is stated in article 6 of law number 8 of 1999 concerning consumer protection ("Consumer Protection Law ”). Based on the things mentioned above, PT Shopee Indonesia has issued a new payment method, namely COD Check First, which is a method where buyers are allowed to open the package before paying for the product to the courier and return it on the spot to the courier if it does not match the product description/photo. So the author needs to do further research regarding the fulfillment of the rights of business actors using this method. This research was conducted through juridical-empirical research, using a qualitative approach. This research was conducted through a data collection method in the form of a documentary study. Meanwhile, the technique applied is qualitative analysis which is then presented descriptively.